Effects and Mechanism of Salvianolic Acid B on the Injury of Human Renal Tubular Epithelial Cells Induced by Iopromide - Shu-Jun Dong; Xin-Yue Gao; Ming-Xin Pei; Ting Luo; Dong Fan; Yan-Ling Chen; Jun-Feng Jin; Xiao-Duo Zhao (Frontiers Media S.A., 2021)
With the increasing application of medical imaging contrast materials, contrast-induced nephropathy (CIN) has become the third major cause of iatrogenic renal insufficiency. CIN is defined as an absolute increase in serum creatinine levels of at least 0.50 mg/dl or an increase >25% of serum creatinine from baseline after exposure to contrast. In this study, the protective effects of salvianolic acid B (Sal B) were detected in human renal tubular epithelial cells (HK-2) exposed to iopromide. The results showed that different concentrations of Sal B counteract the loss of cell viability induced by iopromide, and reduce cell apoptosis, the reactive oxygen species (ROS) levels, and the levels of endoplasmic reticulum stress (ERS)-related and apoptosis-related proteins such as p-IRE-1α, p-eIF-2α/eIF-2α, p-JNK, CHOP, Bax/Bcl-2, and cleaved caspase-3. In addition, Sal B at a concentration of 100 μmol/L inhibited ERS and reduced cell damage to a similar extent as the ERS inhibitor 4-PBA. Importantly, treatment with Sal B could abolish the injury induced by ERS agonist tunicamycin, increasing cell viability and the mitochondrial membrane potential, as well as significantly reducing ROS levels and the expression of Bax/Bcl-2, cleaved-caspase-3, GRP78, p-eIF2α, p-JNK, and CHOP. These results suggested that the protective effect of Sal B against HK-2 cell injury induced by iopromide may be related to the inhibition of ERS.